Increased Blinking May Be a Precursor of Blepharospasm: A Longitudinal Study - Conte, Antonella (Mov Disord Clin Pract, 2017)
BACKGROUND: The objective of this 5‐year longitudinal study was to investigate whether patients with increased blinking develop orbicularis oculi muscle spasms. METHODS: Eleven patients who initially manifested increased blinking alone were clinically and neurophysiologically re‐evaluated 5 years later. RESULTS: By the 5‐year follow‐up assessment, 9 of the 11 patients had developed orbicularis oculi muscle spasms. The blink reflex recovery cycle became abnormal, whereas somatosensory temporal discrimination, which already was abnormal at the first evaluation, did not significantly change. CONCLUSIONS: Our longitudinal study demonstrates that increased blinking may precede blepharospasm and that an abnormal blink reflex recovery cycle reflects the development of orbicularis oculi muscle spasms.